Lack of transparency in clinical trials: a call for action - Ramírez, Jorge H (Colombia Medica, 2013)
The purpose of pharmacological and non-pharmacological medical interventions are maintenance of good health, delay pathology and rehabilitate patients with disability. Because any intervention have the risk of adverse effects, physicians have to weigh benefits against harms before deciding the best treatment for the patient condition, a practice of rational prescription supported by high-quality evidence from randomized clinical trials and meta-analysis. Non-rational prescription of therapeutic interventions could result in severe adverse reactions. These unwanted effects could lead to increased patient visits to emergency rooms, prolonged hospitalizations, disability, loss of productivity days and patient death. Adverse reactions increase health care system costs and often lead to legal actions against physicians, hospitals, and pharmaceutical companies.